Lockdown Accounting - Charles Gottlieb; Jan Grobovsek; Markus Poschke; Fernando Saltiel (Institute of Labor Economics (IZA), 2020)
We measure the effect of lockdown policies on employment and GDP across countries using individual- and sector-level data. Employment effects depend on the ability to work from home, which ranges from about half of total employment in rich countries to around 35% in poor countries. This gap reflects differences in occupational composition, self-employment levels, and individual characteristics across countries. GDP effects of lockdown policies also depend on countries' sectoral structure. Losses in poor countries are attenuated by their higher value-added share in essential sectors, notably agriculture. Overall, a realistic lockdown policy implies GDP losses of 20-25% on an annualized basis.
Keywords: O11; O14; J21; 330; COVID-19; work from home; structural change